1971
DOI: 10.1159/000152439
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Variants of Human Phosphoglucose Isomerase

Abstract: Eight rare variants of human PGI have been discovered during a survey of 3,300 blood samples from various parts of the world. Seven of the 8 variants had altered electrophoretic mobilities. One of these variants was only discovered by the use of a second buffer system. Two of the 8 variants had half the normal level of activity in red cells and white cells. Apart from the partial deficiency of 2 of the variants, the 8 variant phenotypes were not found to differ significantly in any of the following properties:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1975
1975
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 5 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…Since this discovery there have been reports of rare genetically determined variants or variants with low catalytic activities from various populations of the world Fitch et al, 1968;Paglia et al, 1969;Shinoda, 1970; Tariverdian et aI., 1970;Welch 1971;Luan Eng and Welch, 1972;Sanpitak et aL, 1973; Nakashima et aI., 1973;Isacchi et al, 1979), most of which concerns the sporadic occurrence of one or two of the nine heterozygotic types originally described in addition to the usual homozygous phenotype PGI-1. The exceptions are the heterozygous phenotypes PGI 3-1 and 4-1 which are of particular interest in Asiatic populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this discovery there have been reports of rare genetically determined variants or variants with low catalytic activities from various populations of the world Fitch et al, 1968;Paglia et al, 1969;Shinoda, 1970; Tariverdian et aI., 1970;Welch 1971;Luan Eng and Welch, 1972;Sanpitak et aL, 1973; Nakashima et aI., 1973;Isacchi et al, 1979), most of which concerns the sporadic occurrence of one or two of the nine heterozygotic types originally described in addition to the usual homozygous phenotype PGI-1. The exceptions are the heterozygous phenotypes PGI 3-1 and 4-1 which are of particular interest in Asiatic populations.…”
Section: Discussionmentioning
confidence: 99%
“…The exceptions are the heterozygous phenotypes PGI 3-1 and 4-1 which are of particular interest in Asiatic populations. In both the studies from London (Detter et al, 1968;Welch, 1971) the Asiatic Indians showed an appreciable frequency of the variant PGI 3-1 and subsequent studies of indigenous samples confirmed that the PGI a allele attains polymorphic frequencies in certain populations of India. Indeed, the relatively high frequency of this allele led to the detection of the homozygous phenotype PGI-3 (Papiha et aL, 1974).…”
mentioning
confidence: 85%
“…It interconverts glucose 6-phosphate and fructose 6-phosphate, hence plays a central role in both the glycolysis and the gluconeogenesis pathways. PGI deficiency in humans is an autosomal recessive genetic disorder that has the typical manifestation of nonspherocytic hemolytic anemia of variable clinical expression (1,2). The serum activity of human PGI serves as a tumor marker in cancer patients (3,4) and elevation in PGI activity is closely correlated with metastasis (5,6).…”
mentioning
confidence: 99%
“…PGI deficiency in humans leads to nonspherocytic hemolytic disease (1,2). In addition, the serum activity of PGI has been established as a tumor marker in human cancer patients (3,4), and elevation in PGI activity is closely correlated with metastasis (5,6).…”
mentioning
confidence: 99%